Developing an international public health cooperation mechanism for the cruise industry - Wu, Wei; Li, Lu (Frontiers in Marine Science, 2022)
The cruise industry has suffered heavy setbacks owing to the COVID-19 pandemic outbreak. Domestic and global pandemic control measures—involving rules varying across countries as well as distinct legal systems—were escalated. We aimed to illustrate the need to establish a public health cooperation mechanism for the cruise industry. First, we analyzed the legal dilemma pertaining to pandemic prevention and control in cooperative situations; namely, the legal loopholes in the prevention, control, and rescue of cruise ships. Second, we focused on international collaboration during cruise ship rescues amid the pandemic, exploring solutions for current industry problems. Third, by analyzing Chinese practices in cruise-related areas, this paper guides the development of a public health cooperation mechanism for the cruise industry. In sum, we call upon the international community to develop such a mechanism within the scope of international law in terms of public health security and pandemic prevention. Research methodology: This is a practical research paper. Per our analysis of the United Nations Convention on the Law of the Sea and International Health Regulations of the World Health Organization, we studied the global legal issues pertaining to cruise epidemic prevention and control by sorting out legal regulations. We conclude that an international cooperation mechanism for cruise epidemic prevention and control should be established to ensure the cruise industry’s sustainable development.